THE RESULTS OF RESEARCH OF THERMAL-CYCLE LONGEVITY OF HEATPROOF MATERIALS OF GAS TERBINE ENGINES - Кулик, М. С.; Кучер, О. Г.; Ковешніков, М. О.; Дубровський, С. С.; Петрук, Я. А (Science-based technologies, 2009)
Considered resource features high-temperature materials of gas turbine engines (GTE) and units (GTU) in acceleratedtest thermocyclic. The possibility of application of calculation methods based on a model thermocyclicdurability and verified the hypothesis of a linear sum damage, where aN ≠1 , and be in range aN ,=0,1-0,35 .